ANALISIS WACANA VAN DIJK PADA LIRIK LAGU IRGAA TANI (MY HEART WILL GO ON) (Universitas Negeri Semarang, 2012)
he purpose of this study was to describe the structure contained in the lyrics of the song so that people, especially farmers Irgaa song lovers and Arabic language learners can learn, understand and enjoy of intent contained in the lyrics of the song as well as aspects of language in it. Results of this study indicate that the structure contained in the lyrics of the song are Irgaa farmer; macro structure that contains thematic elements suggests that this song about the love story theme song writer to someone who are separated by distance. Superstructure that contains elements of the schematic shows the title / lead and the story of the song lyrics. Microstructure contains elements of semantic, syntactic, stylistic and rhetorical. Semantic elements of the song shows the background, detail and meaning of the lyrics of the song. Syntactic elements of the song contains sentence patterns, coherence and pronoun. Stylistic elements indicate the lexicon of the song lyrics. While the rhetorical elements of the song shows graphics and metaphors that support the beauty of the song. This study also compared the lyrics of the song Irgaa farm with the original song My heart will go on, and the results showed that the song is not a direct translation Irgaa farmer of the song, but there are also cultural elements that influence the farmer Irgaa lyrics.